Contextual Interpretation Of Asghar Ali Engineer : Efforts To Reconstruct Nash On The Women Position In Primordial Society - Rifqi Aulia Rahman; Azwar Annas; Chairani Astina; Umi Sumbulah (MUWAZAH : jurnal kajian gender, 2024)
This study aims to describe how Asghar Ali Engineer reconstructed the position of women in the traditions of primordial society through a contextual reinterpretation of the texts of the Qur’an. This research is of the library (Library Research) type, involving examination and review of data originating from library sources. There are two sources of data: primary data taken from written works by Asghar Ali Engineer, and secondary data obtained from books and journal articles that are aligned with the theme of women's liberation. The results of this study indicate a typology of Asghar Ali Engineer's thought in viewing women, which differs significantly from other thinkers. This distinction arises for two reasons: firstly, he addresses the issues of perspectives that have evolved in the Islamic world regarding women, not solely from a fiqh standpoint but also encompassing philosophical, anthropological, sociological, and historical aspects. Secondly, he presents his writings within the context of the socio-cultural challenges encountered by the Islamic world in modern times. Asghar Ali Engineer argues that Islamic teachings aim to establish a balanced life between men and women, despite historical dominance of the male role that has perpetuated doctrines of inequality between genders.